ANALYZE CRITICAL THINKING SKILLS AND SCIENTIFIC ATTITUDE IN PHYSICS LEARNING USED INQUIRY TRAINING AND DIRECT INSTRUCTION LEARNING MODEL - Dede Parsaoran Damanik; Nurdin Bukit (Universitas Negeri Medan, 2013)
This study was aimed to determine the differences: (1) the difference of critical thinking skills of students' that using Inquiry Training and Direct Instruction. (2) The difference of critical thinking skills among students who at high scientific attitude and students who at low scientific attitude. (3) To see if there is interaction between inquiry learning model of the scientific attitude students' to increase the ability to critical thinking. This is a quasi experimental research. Which students of private junior high school Two Raya Kahean District Simalungun. Population choose random sample of each class. Instrument used consisted of: (1) test the scientific attitude of students through a questionnaire with 25 statements questionnaire number (2) test the critical thinking skills in the form of descriptions by 9 questions. The data were analyzed according to ANAVA. It showed that: (1) There are differences in students' critical thinking of skills achievement Inquiry Training model and Direct Instruction model, (2) there was a difference of students' critical thinking in scientific attitude at high is better than who thought there is a difference of students' critical thinking in scientific attitude at low. (3) There was no interaction between Inquiry Training model and Direct Instruction with the scientific attitude students' to increase student’s critical thinking of skills.